Verbal and visual strategies in nonfiction picturebooks Theoretical and analytical approaches - Goga, Nina; Hoem Iversen, Sarah; Anne-Stefi, Teigland (Scandinavian University Press (Universitetsforlaget), 2021)
This edited volume presents new approaches to better understand how knowledge is presented verbally and visually in children's and young adult nonfiction picturebooks. Nonfiction for children and young adults has existed alongside fiction ever since the very first texts for children appeared. However, in the field of children's literature, there are few critical, theoretical and analytical studies on nonfiction. The chapters in this edited volume demonstrate increased international interest and attention to the variety of nonfiction for children and young adults generally and nonfiction picturebooks in particular. The present volume brings together contributors from different countries and different academic disciplines; they represent a diversity of academic cultures. Together the chapters propose typologies, models, and analytical tools for encountering and interpreting both contemporary and historical nonfiction picturebooks and contribute to increased understanding of verbal and visual complexity in nonfiction picturebooks.